Learning kits as online learning guidelines in Master of Early Childhood education programme - Mahani Abdul Malik; Aliza Ali (2019)
The master degree programme in early childhood education is a postgraduate degree programme in Open University Malaysia (OUM) designed for adult students wishing to further their studies in early childhood online. The learning kit was organised to become a guide and companion to students learning adventure in this programme. Thus this paper discusses the use of learning kit as online learning guideline for students enrolled in the Master of Early Childhood Education (MECHE) programme in OUM. This paper will also describe how learning kit can be used to assist online students in their studies for one semester. In this study, a total of 20 students from MECHE programme were selected purposively. Quantitative data was taken from questionnaires and qualitative data was taken through interviews and open ended questions. The data was analysed using the thematic analysis. The result showed that the students found the learning kit easily accessible and helpful in guiding them to study in this course. (Abstract by authors)